MOBILIZATION OF DEVELOPMENT CAPITAL IN EAST NUSA TENGGARA: LEADERSHIP OF GOVERNOR VIKTOR BUNGTILU LAISKODAT - Pius Rengka; Daniel Daud Kameo; Intiyas Utami; Wilson M.A. Therik (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study examines the social, political, and economic changes in East Nusa Tenggara Province during the leadership of Governor Viktor Bungtilu Laiskodat (2018–2023). As a marginal region, East Nusa Tenggara presents complex development challenges that demand an adaptive leadership model. Utilizing Pierre Bourdieu's theory of capital—social, economic, and cultural—this research analyzes how Governor Viktor Bungtilu Laiskodat’s strategies interacted with the local community’s habitus. A qualitative method was employed to explore the dynamics of the changes that occurred. The main findings include: (1) the strengthening of social capital through empowerment programs such as "Plant Corn, Harvest Cattle" (TJPS); (2) bureaucratic reforms that fostered more transparent and effective governance; and (3) infrastructure development that accelerated mobility, reduced isolation, and encouraged socio-economic transformation. The study reveals that leadership in marginalized areas requires the capacity to contextually mobilize local capital to achieve inclusive and sustainable development. This research contributes theoretically to the literature on political leadership in marginal regions and offers practical implications for the formulation of context-based development policies.